Susceptibility variation to the main pathogens of Crassostrea gigas at the larval, spat and juvenile stages using unselected and selected oysters to OsHV-1 and/or V. aestuarianus - Dégremont, Lionel; Morga, Benjamin; Maurouard, Elise; Travers, Marie-Agnes (Journal of Invertebrate Pathology, 2021)
International audience French commercial hatcheries are massively producing Crassostrea gigas selected for their higher resistance to OsHV-1, and soon should also implement selection for increasing resistance to Vibrio aestuarianus. The first objective of this study was to optimize the breeding programs for dual resistance to OsHV-1 and V. aestuarianus to determine the earliest life stage for which oysters are able to develop disease resistance. Wild stocks and selected families were tested using experimental infections by both pathogens at the larval, spat and juvenile stages. Oyster families could be evaluated for OsHV-1 as soon as the larval stage by a bath method, but this only highlighted the most resistant families; those that showed the highest resistance to V. aestuarianus could be determined using the cohabitation method at the juvenile stage. The second objective of this study was to determine if selection to increase/decrease the resistance to OsHV-1 and V. aestuarianus could have an impact on other major pathogens currently detected in hatchery at the larval stage, and in nursery and field at the spat/juveniles stages (V. coralliilyticus, V. crassostreae, V. tasmaniensis, V.neptunius, V. europaeus, V. harveyi, V. chagasi). No relationship was found between mortality caused by V. aestuarianus/OsHV-1 and the mortality caused by the other virulent bacterial strains tested regardless the stages, except between OsHV-1 and V. tasmaniensis at the juvenile stage. Finally, miscellaneous findings were evidenced such as (1) bath for bacterial challenges was not adapted for spat, (2) the main pathogens at the larval stage were OsHV-1 and V. coralliilyticus using bath, while it was V. coralliilyticus, V. europaeus, and V. neptunius at the juvenile stage by injection, and (4) variation in mortality was observed among families/wild controls for all pathogens at larval and juvenile stages, except for V. harveyi for larvae.